Rehabilitación y mantenimiento de una edificación comercial ubicada en el barrio Sociego al sur de la ciudad de Bogotá D.C. (2021)
Within the research project, a series of pathologies were located in a building located in the Sosiego neighborhood, south of the city of Bogota. The building was built around the 80's and currently presents lesions related to humidity, erosions and detachments in the roofs and walls on the two floors that make up the house; these pathologies can affect its structural system; making it vulnerable to seismic level, increasing the level of danger of a possible collapse or collapse, therefore, what would be the solution to rehabilitate the commercial building located in the Sosiego neighborhood? With the objective of evaluating the present pathologies and analyzing its structural vulnerability in order to carry out a diagnosis for its rehabilitation that relates the social, economic and social spheres to achieve a sustainable development of the system. To achieve this, a recognition and identification of the present symptoms (pre-diagnosis) of the present pathologies will be carried out, and with the help of the seismic resistant standard (NSR-10) its seismic vulnerability will be evaluated to elaborate the diagnosis and treatment proposal.